An evaluation of asymmetric interfaces for bimanual virtual assembly with haptics. Issue 4 (November 2016) - Carlson, Patrick; Vance, Judy; Berg, Meisha
Abstract Immersive computing technology provides a human–computer interface to support natural human interaction with digital data and models. One application for this technology is product assembly methods planning and validation. This paper presents the results of a user study which explores the effectiveness of various bimanual interaction device configurations for virtual assembly tasks. Participants completed two assembly tasks with two device configurations in five randomized bimanual treatment conditions (within subjects). A Phantom Omni® with and without haptics enabled and a 5DT Data Glove were used. Participant performance, as measured by time to assemble, was the evaluation metric. The results revealed that there was no significant difference in performance between the five treatment conditions. However, half of the participants chose the 5DT Data Glove and the haptic-enabled Phantom Omni® as their preferred device configuration. In addition, qualitative comments support both the preference of haptics during the assembly process and comments confirming Guiard's kinematic chain model.